Mechanisms of Single-Walled Carbon Nanotube Nucleation, Growth and Chirality-Control: Insights from QM/MD Simulations - Page, Alister J.; Chandrakumar, Krs; Wang, Ying; Irle, Stephan; Morokuma, Keiji (IntechOpen, 2011)
None